Optimum insulation thicknesses and energy conservation of building thermal insulation materials in Chinese zone of humid subtropical climate. (January 2020) - Huang, Huakun; Zhou, Yijun; Huang, Renda; Wu, Huijun; Sun, Yongjun; Huang, Gongsheng; Xu, Tao
Highlights: A full life cycle model is established for economic analysis of insulation materials. The optimum insulation thickness of super-insulated aerogels is determined. Energy-saving and greenhouse-gas emission for optimized insulation thickness are evaluated. A maximum annual heat load reduction of 18% is achieved with the optimum aerogel insulation. Abstract: Implementing thermal insulation on the building has been acknowledged as a highly effective way to achieve cost-effective energy conservation. For implementing thermal insulation, a key problem is the proper selection of wall insulation in terms of material types and optimum thicknesses because it is challenged to balance energy-saving effects and economic benefits. To address this problem, we investigated the new aerogel super-insulation material for building-energy-conservation application in this paper. Specifically, we took a typical office building of humid subtropical climate as a model, established a whole-life-cycle-assessment model to exploit the optimum economic thickness, and further evaluated the energy-saving rate, economic benefits, the greenhouse-gas emissions, etc. Besides, we compared the super-insulated aerogel with four commonly-used insulation materials, i.e., expanded polystyrene, extruded polystyrene, foamed polyurethane, and glass fibers. Experimental results showed that aerogel had the minimum optimum thickness of 3.7 mm. When aerogel was implemented with the optimum thickness, the annual cooling and the heating load for the hollow shale brick building were reduced by 7.5% and 18.2%, respectively. Additionally, compared with the other materials, aerogel achieved a faster reduction for greenhouse-gas emissions as the thickness increased. The aerogel insulation could lead to lower carbon emissions, e.g., CO2 (8.169 kg/(m 2 yr)) emissions with LPG fuel, and thus would be more preferable for environmental protection. The building energy simulations employed can be further strengthened in the future by considering the effect of urban microclimates and actual internal heat gains in offices.